Penggunaan Teknologi Augmented Reality Dalam Mempelajari Sistem Tata Surya dengan Android - Aswin Fitriansyah (LPPM, 2018)
Abstract. In the history of human life, science is one of the bridges of man to perfection. The human tendency to become pious makes it always move forward to become a better creation day by day. One of the many dynamic movements of humans is reflected in the development of technology and information that helps human work to be more effective and efficient, especially in the application of learning media. Based on this reason, an Augmented Reality application was developed in the learning of the solar system. Through the analysis and design of application infrastructure built using the waterfall method, the analysis stages include system weakness analysis and system requirements analysis, design or design which includes a modeling system using flowchart. From this study produced an Andorid based solar learning Augmented Reality application.Keywords: Solar System, System, Android